The quadratic formula tells you the solution to
ax^2 + bx + c = 0
is given by
x = (-b ± √(b^2 - 4ac))/(2a)
You have an equation in which a=6, b=3, c=-18, so the formula gives
x = (-3 ± √(3^2 - 4(6)(-18))/(2*6)
x = (-3 ± √(9+432))/12
x = (-3 ± √441)/12
x = (-3 ± 21)/12
x = {-24/12, 18/12}
x = {-2, 3/2}
ax^2 + bx + c = 0
is given by
x = (-b ± √(b^2 - 4ac))/(2a)
You have an equation in which a=6, b=3, c=-18, so the formula gives
x = (-3 ± √(3^2 - 4(6)(-18))/(2*6)
x = (-3 ± √(9+432))/12
x = (-3 ± √441)/12
x = (-3 ± 21)/12
x = {-24/12, 18/12}
x = {-2, 3/2}